Quercetin modulates transcription of the apoptotic and CatSper genes and optimises post thaw viability and kinematics of buck spermatozoa - Alok Kumar; J. K. Prasad; Nishant Kumar; Sonika Verma; Mukul Anand; Amrita Behera; Ajeet Kumar; Jitendra Tiwari; Rahul Dhariya; Sumit Singhal; Vishal Yadav (Scientific Reports)
Abstract Oxidative stress during semen processing affects sperm membrane integrity, leading to compromised sperm membrane functions and kinematics, often resulting in reproductive losses. The first objective of the present study explored the effect of Quercetin (QUE) on seminal parameters, i.e., total antioxidant capacity (TAC), as well as sperm viability, DNA fragmentation, kinematics, intracellular calcium, and apoptosis. The second objective evaluated fold changes in the transcription of apoptotic regulatory (Bax, Bad, Bcl2, Bcl2L1, Fas, FasL, and Caspase 3, 8, 9, and 10) and calcium-regulating CatSper-1,2,3 and 4 genes of the buck spermatozoa. The final objective was fertility trial of negative control and best-performing treatment group. The study analysed 36 ejaculates from 6 bucks, each ejaculate was then divided into 5 parts and extended using TRIS extender with different concentrations of QUE. The negative control (C) consists of extended semen without the addition of QUE, whereas positive control (T1) had been added with vitamin E at a concentration of 3 mmol/mL. Furthermore, treatment groups 2, 3, and 4 (T2, T3, T4) were supplemented with 10, 20, and 30 µmol of QUE/mL of extended semen. The samples at the post-thaw stage were evaluated for seminal parameters as described in the objectives. Group T3 supplemented with 20 µmol/mL QUE was observed with the best results. QUE at 20 µmol/mL concentration significantly enhanced semen TAC along with various sperm parameters, i.e., viability, kinematics, intracellular calcium and plasma membrane fluidity. QUE at 20 µmol/mL concentration also downregulated pro-apoptotic and upregulated anti-apoptotic genes. Similarly, QUE downregulated caspase family genes and upregulated CatSper genes. Field fertility trials showed improved conception rates in the treatment group. QUE-induced control of oxidants might have contributed to higher TAC and viability. The upregulation of anti-apoptotic and downregulation of pro- and other apoptotic regulatory genes, as well as the upregulation of CatSper genes, suggest a regulatory effect of QUE on sperm apoptosis, and calcium homeostasis. Lower proportion of apoptosis and higher normal intracellular calcium, as estimated through flow cytometry, further validated our findings. Our field fertility trial yielded 58.3% conception rate in the treatment group as compared to 27.6% in the control group. QUE at 20 µmol/mL concentration significantly improved the antioxidant capacity, intra-cellular calcium concentration, and kinematics of goat sperm and subsequently resulted in better fertility as compared to control.